2001
DOI: 10.1002/bit.1117.abs
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of pyruvate metabolism in Lactococcus lactis

Abstract: The pyruvate metabolism in the lactic acid bacterium Lactococcus lactis was studied in anaerobic cultures under transient conditions. During growth of L. lactis in continuous culture at high dilution rate, homolactic product formation was observed, i.e., lactate was produced as the major end product. At a lower dilution rate, the pyruvate metabolism shifted towards mixed acid-product formation where formate, acetate, and ethanol were produced in addition to lactate. The regulation of the shift in pyruvate meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…It is interesting to note that the accumulation of glucose at pH 4?7 restores homolactic fermentation, as has been shown under chemostat conditions at high growth rates (Thomas et al, 1979). The regulation of pyruvate formate lyase (PFL) may contribute to this metabolic shift since this enzyme has been identified as a key enzyme under neutral conditions (Melchiorsen et al, 2001). Furthermore, PFL is known to be more sensitive to low pH than lactate dehydrogenase (Asanuma & Hino, 2000).…”
Section: Discussion Acid Stress Damagesmentioning
confidence: 99%
“…It is interesting to note that the accumulation of glucose at pH 4?7 restores homolactic fermentation, as has been shown under chemostat conditions at high growth rates (Thomas et al, 1979). The regulation of pyruvate formate lyase (PFL) may contribute to this metabolic shift since this enzyme has been identified as a key enzyme under neutral conditions (Melchiorsen et al, 2001). Furthermore, PFL is known to be more sensitive to low pH than lactate dehydrogenase (Asanuma & Hino, 2000).…”
Section: Discussion Acid Stress Damagesmentioning
confidence: 99%
“…pfl expression in other bacteria is known to be influenced by galactose and anaerobiosis (33,34). Indeed, in strain D39 in anaerobiosis, SPD0420 expression increased nearly ninefold in galactose relative to that for glucose-grown bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in other lactic acid bacteria, low pH and excess supplies of energy reduced pfl mRNA levels, while the level of ldh mRNA increased (3). The regulation of PFL is allosterically controlled in L. lactis by the glycolytic intermediates fructose 1,6-bisphosphate, glyceraldehyde-3-phosphate (GAP), and dihydroxyacetone phosphate, which are strong inhibitors of PFL (33).…”
mentioning
confidence: 99%
“…These organic acids were suggested to substitute the requirement of true hiochi-bacilli for acetate which is generally scarce in sake 41 . However, this hypothesis remains to be tested, since these organic acids are increasingly implicated in energy production in LAB 20,55,62,63,82,86 and presumably help LAB survive in inhospitable environments. Interestingly, it has been shown that the presence of ethanol in high concentrations considerably increases the thickness of the cell wall of true hiochi-bacilli.…”
Section: Unique Features Of Sake and Beer Spoilage Lab Ethanol Toleramentioning
confidence: 99%